Evaluation of possible biomarkers for caries risk in children 6 to 12 years of age (2021)
Background: Electrolytes, proteins, and other salivary molecules play an important role in tooth integrity and can serve as biomarkers associated with caries. Objective: To determine the concentration of potential biomarkers in children without caries (CF) and children with caries (CA). Methods: Unstimulated saliva was collected, and the biomarkers quantified in duplicate, using commercial Enzyme Linked Immunosorbent Assay (ELISA) kits to determine IgA, fibronectin, cathelicidin LL-37, and statherin levels, as well as colorimetric tests to detect formate and phosphate. Results: Significantly higher concentrations of statherin was detected in the CF group (Median: 94,734.6; IQR: 92,934.6–95,113.7) compared to the CA2 group (90,875.0; IQR: 83,580.2–94,633.4) (p = 0.03). Slightly higher median IgA (48,250.0; IQR: 31,461.9–67,418.8) and LL-37 levels (56.1; IQR 43.6–116.2) and a lower concentration of formate were detected in the CF group (0.02; IQR 0.0034–0.15) compared to the group with caries (IgA: 37,776.42; IQR: 33,383.9–44,128.5; LL-37: 46.3; IQR: 40.1011–67.7; formate: 0.10; IQR: 0.01–0.18), but these differences were not statistically significant. Conclusion: The fact that these compounds have been identified as good markers for caries among European adults highlights the difficulty of identifying universal biomarkers that are applicable to all ages or to different populations.